2007
DOI: 10.1111/j.1365-2265.2007.03066.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty fish and supplements are the greatest modifiable contributors to the serum 25‐hydroxyvitamin D concentration in a multiethnic population

Abstract: SummaryObjective Because vitamin D synthesis is lower in a heavily pigmented skin than in a lighter skin, the relative contribution of determinants to the vitamin D concentration might differ between ethnic groups. The aim of this study was to assess the prevalence of vitamin D deficiency and the relative contribution of vitamin D consumption and exposure to sunlight to the vitamin D concentration in a multiethnic population. Design Cross-sectional study. Modifiable, significant determinants (standardized regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 36 publications
6
59
2
Order By: Relevance
“…Serum 25(OH)D was lower than 25 nmol/l in 40% of non-Western immigrants in the Netherlands [69]. Pregnant non-Western women even carry a higher risk: a study in midwife practices in The Hague showed a serum 25 (OH)D lower than 25 nmol/l in more than 80% of Turkish and Moroccan immigrants.…”
Section: Europementioning
confidence: 99%
See 2 more Smart Citations
“…Serum 25(OH)D was lower than 25 nmol/l in 40% of non-Western immigrants in the Netherlands [69]. Pregnant non-Western women even carry a higher risk: a study in midwife practices in The Hague showed a serum 25 (OH)D lower than 25 nmol/l in more than 80% of Turkish and Moroccan immigrants.…”
Section: Europementioning
confidence: 99%
“…Therefore, both latitude and seasons influence the degree of possible solar radiation a population may receive. The literature reports strong evidence that hypovitaminosis D is greater in winter months for all age groups in Asia [25,26], Europe [69,72,82], Latin America [79], Middle East [91], North America [153], and Oceania [142]. However, in very hot countries and where the majority of women wear veils, vitamin D levels were not significantly higher and were even lower in the summer months, as these women avoided the heat and sun by staying indoors [101,105].…”
Section: Latitude and Seasonmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the prevalence of deficiency (<50 nmol/l 25OHD3) in a Caucasian Dutch population is about 23% in summertime [6]. The 25OHD3 level decreases in wintertime as expected, since on our latitude UV radiation is insufficient for vitamin D formation in the skin from November up till and including March [1].…”
Section: Discussionmentioning
confidence: 99%
“…asian Indian immigrants in northern climates have lower serum 25(oH)D than Caucasians and have a tendency to develop rickets and osteomalacia; in the Netherlands over 51% of sas were vitamin D-deficient (25(oH)D <25nmol/l) 98 . low vitamin D concentrations are related to increased risk of T2D, affecting pancreatic insulin secretion and insulin resistance 91,99 .…”
Section: Vitamin Dmentioning
confidence: 99%